Physicochemical and toxicological characteristics of particulate matter emitted from a non-road diesel engine: Comparative evaluation of biodiesel-diesel and butanol-diesel blends - Zhang, Zhi-Hui; Balasubramanian, Rajasekhar (Journal of hazardous materials, 2014)
Combustion experiments were conducted to evaluate the effects of using blends of ultralow sulfur diesel (ULSD) with biodiesel or n-butanol on physicochemical and toxicological characteristics of particulate emissions from a non-road diesel engine. The results indicated that compared to ULSD, both the blended fuels could effectively reduce the particulate mass and elemental carbon emissions, with butanol being more effective than biodiesel. The proportion of organic carbon and volatile organic compounds in particles increased for both blended fuels. However, biodiesel blended fuels showed lower total particle-phase polycyclic aromatic hydrocarbons (PAHs) emissions. The total number emissions of particles ≤560nm in diameter decreased gradually for the butanol blended fuels, but increased significantly for the biodiesel blended fuels. Both the blended fuels indicated lower soot ignition temperature and activation energy. All the particle extracts showed a decline in cell viability with the increased dose. However, the change in cell viability among test fuels is not statistically significant different with the exception of DB-4 (biodiesel–diesel blend containing 4% oxygen) used at 75% engine load.